Small RNA-Mediated De Novo Silencing of Ac/Ds Transposons Is Initiated by Alternative Transposition in Maize. Issue 2 (1st June 2020) - Wang, Dafang; Zhang, Jianbo; Zuo, Tao; Zhao, Meixia; Lisch, Damon; Peterson, Thomas
Abstract: Transposable elements (TEs) are a ubiquitous feature of plant genomes. Because of the threat they pose to genome integrity, most TEs are epigenetically silenced. However, even closely related plant species... Although transposable elements (TEs) comprise a major fraction of many higher eukaryotic genomes, most TEs are silenced by host defense mechanisms. The means by which otherwise active TEs are recognized and silenced remains poorly understood. Here we analyzed two independent cases of spontaneous silencing of the active maize Ac/Ds transposon system. This silencing is initiated by alternative transposition, a type of aberrant transposition event that engages the termini of two nearby separate TEs. Alternative transposition during DNA replication can generate Composite Insertions that contain inverted duplications of the transposon sequences. We show that the inverted duplications of two Composite Insertions are transcribed to produce double-stranded RNAs that trigger the production of two distinct classes of small interfering RNAs: a 24-nt class complementary to the TE terminal inverted repeats and noncoding subterminal regions, and a 21- to 22-nt class corresponding to the TE transcribed regions. Plants containing these small interfering RNA-generating Composite Insertions exhibit decreased levels of Ac transcript and heritable repression of Ac/Ds transposition. Further, we demonstrate that Composite Insertions can heritably silence otherwise active elements in trans . This study documents the first case of transposon silencing induced by alternative transposition and may represent a general initiating mechanism for silencing of DNA transposons.